Music and the play of power in the Middle East, North Africa and Central Asia - Nooshin, Laudan (SOAS musicology series., 2009)
This volume presents the first direct look at the complex relationship between music and power across a range of musical genres and countries. Discourses of power in the region centre on some of the most contested social issues, most notably in relation to nationhood, gender and religion. Individual chapters examine the ways in which music serves as a forum for playing out issues of power, ideology, resistance and subversion. How does music become a space for promoting - or conversely, resisting or subverting - particular ideologies or positions of authority? How does it accrue symbolic power.